Chemerin Level as a Marker in Preeclampsia and its Relation to the Disease Severity and Neonatal Outcome - Ali Mohammed Murad, Marwa Jaafar Sadac (M.B.Ch.B)2; Hanan Hazim Mohammed Noori (M.B.Ch.B, C.A.B.O.G, (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim of study: To detect serum chemerin level in patient with preeclampsia and evaluate the association between maternal serum chemerin, disease severity and neonatal outcome. Patients and Method: A case control study included 100 pregnant women with singleton pregnancy, gestational age of 20 weeks or more, normal fetal morphology, and absence of concomitant diseases, who were collected from inpatient during delivery was conducted in the Department of Obstetrics and Gynecology at Al-Yarmouk Teaching Hospital during the period from 1st of June 2018 till end of May 2019. They were divided into three groups (control, mild preeclampsia, and severe preeclampsia). Patients with history of chronic hypertension, diabetes mellitus, cardiovascular disease, neurological disorder, renal impairment, or premature rapture of membrane were excluded from this study. blood sample was taken from all patients and sent for human chemerin assay. After delivery, birthweight of baby, APGAR scores at one and five mints, neonatal intensive care unit and adult intensive care unit admission, and hospitalization time were also noted. Results: There were no statistically significant differences between the study groups in age, BMI level, and parity. Chemerin level was significantly elevated in patients with severe preeclampsia (435.06 ng/ml) and mild preeclampsia (227.49 ng/ml) than that in non-preeclamptic patients (202.6 ng/ml). It was negatively correlated with each of gestational age, birth weight, Apgar score at one and five minutes. While it was positively correlated with admission’s duration. Serum chemerin > 228.5 ng/ml is predictive for diagnosis of preeclampsia and level > 380.9 ng/ml is indicator for severe preeclampsia. Conclusion: Chemerin may play a role in the pathogenesis of preeclampsia as maternal serum chemerin level was significantly higher in patients with preeclampsia